Multidimensional biological activities of resveratrol and its prospects and challenges in the health field - Yu, Xi; Jia, Yuanqiang; Ren, Feiyue (Frontiers in Nutrition, 2024)
Resveratrol (RES) is a naturally occurring polyphenolic compound. Recent studies have identified multiple potential health benefits of RES, including antioxidant, anti-inflammatory, anti-obesity, anticancer, anti-diabetic, cardiovascular, and neuroprotective properties. The objective of this review is to summarize and analyze the studies on the biological activities of RES in disease prevention and treatment, as well as its metabolism and bioavailability. It also discusses the challenges in its clinical application and future research directions. RES exhibits significant potential in the prevention and treatment of many diseases. The future direction of RES research should focus on improving its bioavailability, conducting more clinical trials to determine its effectiveness in humans, and investigating its mechanism of action. Once these challenges have been overcome, RES is expected to become an effective health intervention.